1997
DOI: 10.1093/oxfordjournals.pcp.a029125
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of an Aquaporin Promoter from Mesembryanthemum crystallinum in Tobacco

Abstract: The promoter region of the MipB gene encoding an aquaporin from Mesembryanthemum crystallinum was isolated and used in a transcriptional fusion to control uidA expression in tobacco. The sequence of the promoter was determined for 2 kb upstream of the translation initiation site. Three start sites were utilized with approximately equal frequency, located 176, 170, and 161 bases, respectively, upstream of the translation initiation site. As judged by analysis of GUS expression, promoter MipB retains its specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…Up to the present, few immunological analyses monitored cell specificity of individual MIPs (Yamamoto et al, 1991;Jones and Mullet, 1995;Kaldenhoff et al, 1995;Sarda et al, 1997). Other analyses reported transcript location using in situ hybridization (Yamada et al, 1995;Sarda et al, 1997;Barrieu et al, 1998;Chaumont et al, 1998) or the analysis of Mip-promoter GUS fusions (Yamamoto et al, 1991;Yamada et al, 1997). We have chosen to present immunological data from root and stem analysis because the signature cell types that distinguish the four proteins for which we generated antibodies are most clearly observed in these tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to the present, few immunological analyses monitored cell specificity of individual MIPs (Yamamoto et al, 1991;Jones and Mullet, 1995;Kaldenhoff et al, 1995;Sarda et al, 1997). Other analyses reported transcript location using in situ hybridization (Yamada et al, 1995;Sarda et al, 1997;Barrieu et al, 1998;Chaumont et al, 1998) or the analysis of Mip-promoter GUS fusions (Yamamoto et al, 1991;Yamada et al, 1997). We have chosen to present immunological data from root and stem analysis because the signature cell types that distinguish the four proteins for which we generated antibodies are most clearly observed in these tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mip genes are seed, root, and leaf specific, and are associated with leaf expansion, root tip elongation, or seedling development (Guerrero et al, 1990;Yamamoto et al, 1991;Hö fte et al, 1992;Jones and Mullet, 1995;Fukuhara et al, 1999). Cell specificity has been reported for some Mip genes based on in situ hybridizations or by monitoring Mip-promoter-controlled uidA (␤-glucuronidase [GUS]) activity (Yamamoto et al, 1991;Jones and Mullet, 1995;Kaldenhoff et al, 1995;Yamada et al, 1995Yamada et al, , 1997Barrieu et al, 1998;Chaumont et al, 1998). Studies on Mip expression have indicated regulation by environmental factors such as drought, salinity, or temperature (YamaguchiShinozaki et al, 1992;Jones and Mullet, 1995;Yamada et al, 1995;Maurel, 1997;Johansson et al, 1998).…”
mentioning
confidence: 99%
“…All of these mechanisms can be affected by water stress, a reduction in the water in the leaf and hence in the vacuoles is a known effect of water stress [25] as is an increase in the concentration of soluble compounds [53]. Moreover, the permeability of the tonoplast increases [54,55] or decreases [56,57] depending on the stress and the species.…”
Section: Impact Of Mild Drought Stressmentioning
confidence: 99%
“…The inhibition of L P by HgCl 2 was similar in magnitude to that caused by hypoxia, and the addition of HgCl 2 to hypoxia-treated cells did not result in further inhibition. We compared the L P of intact cells with that predicted from a model of cortical cells incorporating water flow across both the plasma membrane and the tonoplast using measured values of water permeability from isolated membranes, and found that HgCl 2 has other effects in addition to the direct inhibition of water channels.The cloning and functional expression of aquaporins from higher plants (Maurel et al, 1993(Maurel et al, , 1997a Daniels et al, 1994 Daniels et al, , 1996 Kammerloher et al, 1994;Yamada et al, 1997;Weig et al, 1997; Chaumont et al, 1998; Johansson et al, 1998) has indicated that water flow across intact higher plant membranes could be predominantly through aquaporins. The biophysical evidence for this in higher plants has lagged behind the molecular work, but recent studies have shown that biophysical characteristics of water transport are consistent with water flow occurring predominantly through channels in some membranes.…”
mentioning
confidence: 99%
“…The cloning and functional expression of aquaporins from higher plants (Maurel et al, 1993(Maurel et al, , 1997a Daniels et al, 1994 Daniels et al, , 1996 Kammerloher et al, 1994;Yamada et al, 1997;Weig et al, 1997; Chaumont et al, 1998; Johansson et al, 1998) has indicated that water flow across intact higher plant membranes could be predominantly through aquaporins. The biophysical evidence for this in higher plants has lagged behind the molecular work, but recent studies have shown that biophysical characteristics of water transport are consistent with water flow occurring predominantly through channels in some membranes.…”
mentioning
confidence: 99%